A study on the performance of environmentally benign lubricants at elevated temperatures in bulk metal forming. (October 2015) - Groche, P.; Zang, S.; Müller, C.; Bodenmüller, D.
Abstract: The application of environmentally benign tribological systems becomes more and more important in cold forging operations. However, questions regarding the performance of these systems still oppose a widespread use in industry. Due to severe loads in cold forging, high tool temperatures of up to 200 °C may occur as a result of forming energy and friction in combination with a high output in a short range of time. The temperature at the tool–workpiece interface is even higher, though an exact identification proves to be difficult. Former investigations regarding the influence of the relative velocity indicated that the occurring temperatures are primarily responsible for the decrease of the friction. The paper at hand presents the results of a systematic investigation of the influence of the temperature at the tool–workpiece interface on the performance of environmentally benign tribological systems.